2012
DOI: 10.1007/s11999-012-2351-2
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Method Affects Elution and Strength of High-dose ALBC: A Pilot Study

Abstract: Background High-dose antimicrobial-loaded bone cement (ALBC) is used to treat orthopaedic infections. High-dose ALBC is not commercially available and requires surgeon directed formulation, and there are several different methods used to mix high-dose ALBC. Questions/purposes We asked whether the mixing method affected antimicrobial elution and mechanical properties of high-dose ALBC. Methods ALBC was formulated with Simplex 1 P bone cement and 10 g of vancomycin per batch using one of three mixing methods: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…This large decrease in compressive strength is likely related to the very large volume fraction of 24 vol%. The loss of compressive strength caused by the 300-mg formulation was consistent with previous studies of highdose ALBA with similar volume fractions after 1 day in elution (78-52 MPa for 300 mg voriconazole, 95-59 MPa for 10 g vancomycin) [13]. The average compressive strength of Simplex P without antimicrobial is approximately 85 MPa under identical experimental conditions.…”
Section: Discussionsupporting
confidence: 88%
“…This large decrease in compressive strength is likely related to the very large volume fraction of 24 vol%. The loss of compressive strength caused by the 300-mg formulation was consistent with previous studies of highdose ALBA with similar volume fractions after 1 day in elution (78-52 MPa for 300 mg voriconazole, 95-59 MPa for 10 g vancomycin) [13]. The average compressive strength of Simplex P without antimicrobial is approximately 85 MPa under identical experimental conditions.…”
Section: Discussionsupporting
confidence: 88%
“…The higher-dose formulation released more gentamicin over a longer duration. Release from the higher-dose G-PNDJ formulation is very similar to the release characteristics of high-dose antimicrobial-loaded bone cement over the first week [41] but G-PNDJ does not have the long-duration subtherapeutic release that occurs with antimicrobial-loaded bone cement because it is fully degraded by 4 weeks [50]. It is generally accepted that high-dose antimicrobial-loaded bone cement is indicated for treatment of established infection.…”
Section: Discussionmentioning
confidence: 84%
“…We know that the amount of antimicrobial (or Gd-DTPA) released from cement is affected both by the amount of drug loaded [21,22] and the porosity of the cement [23]. McLaren et al [21] showed relatively similar elution from all of the commercially available ''low-dose'' formulations, although the current study only evaluated Simplex 1 .…”
Section: Discussionmentioning
confidence: 73%